Effect of Subclinical Mastitis on Fibrinogen, Orotic Acid and Some Enzymes in the Milk of Dairy Cows - Sahu, Suresh; Maiti, Sushil Kumar; Raghuvanshi, Pavan Divan Singh (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was undertaken to investigate the effect of subclinical mastitis on some indicators of inflammation in milk, and their  correlation with somatic cell count (SCC) in cattle. A total of 20 lactating cows positive for subclinical mastitis and equal number of  cows negative for subclinical mastitis by both modified California mastitis test (MCMT) and somatic cell count (SCC) were examined  for the levels of fibrinogen, orotic acid and some of milk enzymes. Cows having subclinical mastitis were found to have significantly  higher levels of alkaline phosphatase (ALP), lactate dehydrogenase (LDH) and aspartate amino transferase (AST) activity in the milk  in comparison to the control cows. Fibrinogen and orotic acid levels in subclinical mastitis (SCM) milk were also significantly higher  than that of healthy cows. Milk somatic cell count (SCC) showed highest correlation with ALP ( r = 0.83, P
Keywords: Cattle; Enzymes; Fibrinogen; Milk; Orotic acid; Subclinical mastitis